Comparative proteomic analysis of ventricular and cisternal cerebrospinal fluid in haemorrhagic stroke patients. (January 2023) - Hopkins, Katherine; Price, Benjamin; Ziogas, James; Adamides, Alexios; Mangum, Jonathan
Highlights: First proteomic analysis of cisternal CSF and comparison of ventricular and cisternal CSF composition. First group to successfully quantify d -dimer in CSF using mass spectroscopy. Absence of significant differences between ventricular and cisternal CSF suggests a homogenous environment. Studies analysing CSF for vasospasm biomarkers can confidently analyse ventricular sources. Abstract: Background: Analysis of cerebrospinal fluid (CSF) using mass spectrometry is a relatively novel analytical tool, and comparisons of ventricular and cisternal proteomes are yet to be performed. This may have implications for clinical medicine, particularly in demonstrating continuity of the ventricular system with preserved flow in the presence of ventricular blood. Other uses include the identification of novel biomarkers, including for diagnosis of subarachnoid haemorrhage and of aetiology. The primary objective was therefore to characterise and compare the proteomes of ventricular and CSF after haemorrhagic stroke. Methods: Paired CSF samples were prospectively collected from the optico-carotid cistern and the frontal horn of the lateral ventricle at the time of craniotomy and clipping in 8 patients with haemorrhagic stroke. Six patients had an aneurysmal subarachnoid haemorrhage (aSAH) from a ruptured saccular aneurysm, one patient had an aSAH after rupture of a mycotic aneurysm and one patient had a spontaneous intracerebral haemorrhage (IPH) with an adjacent unruptured saccular aneurysm. Samples were processed and proteins identified and quantified using data-dependent liquid chromatography tandem mass spectrometry (DDA LC-MSMS). Results: There was no systematic difference between the cisternal and ventricular proteomes. However, blinded principal component analysis (PCA) of the cisternal and ventricular samples separated patients according to pathophysiology. Additionally CSF D-Dimer levels were not detected in the IPH patient but were reliably measured in aSAH patients. Conclusions: Ventricular CSF is representative of cisternal CSF after aSAH. CSF proteomic PCA analysis can distinguish between haemorrhage types. CSF D-dimer levels may represent a novel diagnostic marker for aSAH. Label free DDA LC-MSMS CSF analysis may inform possible biomarkers.